Synergism of Ag+ and Na+ in N-acetyl-p-quinoneimine matrix for dual sensing applications - Priyanka Sharma; Mamta Sahu; Mainak Ganguly; Ankita Doi (Scientific Reports)
Abstract A highly fluorescent silver nanostructure was obtained from a commercially available pharmaceutical drug in an alkaline solution. The fluorescence observed was highly selective to Ag⁺, attributed to the in situ formation of Ag⁰ nanostructures. Nanoclusters are usually ≤ 2 nm in size. Microscopic techniques and dynamic light scattering spectroscopy did not find the presence of particles with ≤ 2 nm in our present work. The absence of a plasmon band in absorption spectroscopy and the presence of Ag2–Ag4 in LCMS fragmentations supported the silver giant nanocluster (a larger particle decorating with tiny clusters) with discrete energy levels due to inter-band d–d transition. It ruled out metal-enhanced fluorescence (MEF). Na+ increased the fluorescence intensity of giant clusters due to the natural crystallization and confinement effect. The influence of heat and sunlight was analyzed before and after Na+ inclusion. Thus, Ag+ (linear detection range of 5 × 10− 5 M to 1 × 10− 7 M and limit of detection of 3.6 × 10− 6 M) and Na+ (linear detection range 10− 6 M to 10− 9 M and limit of detection 7.2 × 10− 8 M) dual sensing was made possible in a single pot. The technique can facilitate sustainable water management to control water pollution.